2019
DOI: 10.12688/gatesopenres.13045.2
|View full text |Cite
|
Sign up to set email alerts
|

Access to family planning for youth: perspectives of young family planning leaders from 40 countries

Abstract: Background: With growing populations of young people, low and middle-income countries have renewed focus on reaching both unmarried and married youth with family planning (FP) services. Young people themselves bring an important perspective to guide future programmatic directions. Methods: In October 2018, 207 youth leaders in FP from around the world completed an online survey prior to their participation at the International Conference on Family Planning (ICFP). These youth leaders provided their perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…Spouse or partner was reported as the most influential (80.4%), followed by service providers (44.1%), community health workers (39.2%), and peers/friends (36.3%). A similar question was asked about influencers of contraceptive choice and contraceptive continuation and the pattern of responses was similar (see Underlying data) 19 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spouse or partner was reported as the most influential (80.4%), followed by service providers (44.1%), community health workers (39.2%), and peers/friends (36.3%). A similar question was asked about influencers of contraceptive choice and contraceptive continuation and the pattern of responses was similar (see Underlying data) 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, 85.7% and 78.6% of respondents said it was very or somewhat easy for married youth to get pills and injectables (significantly different than unmarried youth). Further, while 70.2% reported that it was easy for married youth to get implants, 19.7% reported that implants are still somewhat or very hard for this group to get. Condoms were rated easy to get almost equally for unmarried and married youth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilization of family planning methods is determined by factors at the individual, household, and community level, but the geographic pattern of contraceptive use may be associated with in uences at zonal level such as the availability and accessibility of health services in these areas (17). In responding, health actions are needed at each level, from structural, through community settings including schools and health services (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%